2021
DOI: 10.1002/chem.202102089
|View full text |Cite
|
Sign up to set email alerts
|

Azo‐Functionalized Zirconium‐Based Metal−Organic Polyhedron as an Efficient Catalyst for CO2 Fixation with Epoxides

Abstract: Chemical fixation of CO 2 as C1 source at ambient temperature and low pressure is an energy-saving way to make use of the green-house gas, but it still remains a challenge since efficient catalyst with high catalytic active sites is required. Here, a novel monoclinic azo-functionalized Zr-based metalÀ organic polyhedron (Zr-AZDA) has been prepared and applied in CO 2 fixation with epoxides. The inherent azo groups not only endow Zr-AZDA with good solubilization, but also act as basic sites to enrich CO 2 showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The high-resolution spectrum of Zr 3d revealed binding energies of 184.76 and 182.46 eV, corresponding to the two characteristic peaks of the Zr 3d 5/2 and Zr 3d 3/2 orbitals, respectively (Figure 3d). 38 The porous structure of the samples was analyzed by nitrogen adsorption isotherms at 77 K. One can see that both MOP-NH 2 and M@T-X have large specific surface areas and suitable pore sizes (Figures S5 and S6). Furthermore, the pore size distribution curves of MOP-NH 2 showed that the pore size was 0.38 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The high-resolution spectrum of Zr 3d revealed binding energies of 184.76 and 182.46 eV, corresponding to the two characteristic peaks of the Zr 3d 5/2 and Zr 3d 3/2 orbitals, respectively (Figure 3d). 38 The porous structure of the samples was analyzed by nitrogen adsorption isotherms at 77 K. One can see that both MOP-NH 2 and M@T-X have large specific surface areas and suitable pore sizes (Figures S5 and S6). Furthermore, the pore size distribution curves of MOP-NH 2 showed that the pore size was 0.38 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We reacted these ligands with excess zirconocene dichloride (Cp 2 ZrCl 2 , Cp = η 5 -C 5 H 5 ), which was hydrolyzed to 3-connected trinuclear pyramidal Zr 3 O clusters (Cp 3 Zr 3 O­(OH) 3 (Figure a), to afford four discrete tetrahedral structures. Based on these cages, several functional Zr-MOCs were subsequently realized by decorating the cage surface with various functional groups (e.g., NH 2 , , N, ,, NN, imidazolium, SH, SO 2 , SO 3 – , CH 3 , , CC, acrylate, tetrazole, OH, Br, and NO 2 ) for targeted applications. These functional groups have also brought additional benefits such as the improved solubility, sites for cross-linking, and PSM …”
Section: Primary Self-assembly Of Zr-mocsmentioning
confidence: 99%
“…In addition, research into MOPs is often motivated by their higher solubilities relative to MOFs because they are molecular in nature. , ZrMOPs have shown stability in both basic and acidic media and at temperatures up to 300 °C. , The synthesis of ZrMOPs can be done under atmospheric conditions and requires only zirconocene dichloride with a simple dicarboxylate ligand in addition to the solvent, making the process both easy and inexpensive . For these reasons, ZrMOPs have been studied to address a wide range of applications including sensing, catalysis, biomedicine, guest capture, , and gas separation/storage. …”
Section: Introductionmentioning
confidence: 99%